VD_FINDINFO Décision / 2013 / 83 vom 12. September 2012 - VD Tribunal cantonal (2012)
FIXATION DE LA PEINE, CONSTATATION DES FAITS, PRÉSOMPTION D'INNOCENCE | 123 CP, 126 CP, 180 CP, 181 CP, 190 CP, 22 ad 190 CP, 285 CP